An ocean bottom seismic observatory with near real‐time telemetry. Issue 2 (5th February 2016) - Berger, J.; Laske, G.; Babcock, J.; Orcutt, J.
Abstract: We describe a new technology that can provide near real‐time telemetry of sensor data from the ocean bottom without a moored buoy or a cable to shore. The breakthrough technology that makes this system possible is an autonomous surface vehicle called a Wave Glider developed by Liquid Robotics, Inc. of Sunnyvale, CA, which harvests wave and solar energy for motive and electrical power. We present results from several deployments of a prototype system that demonstrate the feasibility of this concept. We also demonstrated that a wave glider could tow a suitably designed ocean bottom package with acceptable loss of speed. With further development such a system could be deployed autonomously and provide real‐time telemetry of data from seafloor sensors. Key Points: A new technology enables seafloor sensors to send data to shore in near real‐time This technology could be used for autonomous deployment of an ocean bottom package Autonomous deployment could reduce overall costs significantly by eliminating the need for ships